Punchinella Little Fella : A celebration of indigenous knowledge in traditional games.
Edna Manley College of the Visual and Performing Arts Colour Museum and (He) Art of the Matter: Taking on Purpose presents Punchinella Little Fella: a celebration of indigenous knowledge in traditional games to be held on Thursday February 22, 2018 - 2:00 p.m.-5:00 p.m. at Bert Rose Studio Theatre. Programme consists of two parts: Part 1-Run up an dung and Part 2-Siddung an lissen.
Posters are located in drawer #1.
Keywords: Arts -- Dance -- Jamaica; Posters -- Jamaica